Impact of corner modification on wind characteristics and wind energy potential over flat roofs of tall buildings. (15th February 2022) - Dai, S.F.; Liu, H.J.; Chu, Y.J.; Lam, H.F.; Peng, H.Y.
Abstract: Wind energy development in built environment is important for the future sustainable cities. The effects of corner modifications (benchmark, recessed, chamfered, and rounded roofs) and wind angles ( θ = 0°, 22.5°, and 45°) over the flat rooftops of tall buildings were investigated through computational fluid dynamics (CFD) simulations. The velocity, turbulence intensity, skew angle, wind energy, and installation of wind turbines over roofs were also examined. The vertical wind profiles over the rooftops showed similar patterns at various corner modifications. The rounded and chamfered roofs showed higher velocities and lower turbulence intensities than the benchmark and recessed roofs, which can be attributed to the smooth flow separation from leading edges and the flow reattachment over the rounded and chamfered roofs. The hub heights were significantly lower at θ = 45° than those at 0° and 22.5°, due to the thinner boundary layer over roofs at θ = 45°. The highest wind energy amplification factor of 2.0 occurred over the rounded roof. The rounded roof was found to be ideal for the installation of wind turbines, due to the high velocity (more energy), low turbulence (small fatigue loads of wind turbines), and low installation height (low cost). Highlights: Flow features and energy over roofs of tall buildings are investigated by CFD. Effect of corner modification (sharp, recess, chamfer, and round) is examined. larger wind angles induce larger zones of higher velocity and lower hub height. Rounded roofs have a great potential for high energy yield and are idea for turbines. Smooth flow separation and reattachment occur on rounded and chamfered roofs.